Challenges in Anesthesia Practice with Kratom - Jirakulsawat, Anchala; Noitasaeng, Papiroon; Noocharoen, Nisa; Apidechakul, Parichad; Vichitvejpaisal, Phongthara (Journal of The Royal Thai Army Nurses, 2023)
Kratom, also known as Mitragyna speciosa, is a plant native to Southeast Asia. Its active ingredients, mitragynine and 7-hydroxymitragynine, affect the central nervous system in a manner similar to opioids; at low doses, kratom can increase work endurance and productivity, but at high doses it can have sedative effects and cause adverse reactions such as digestive and circulatory problems. Withdrawal symptoms, such as uncontrolled behavior, may occur if kratom consumption is stopped, but it is not known to lead to serious crimes. Kratom can also interfere with the liver’s metabolism of other drugs by inhibiting the cytochrome P-450 enzyme. As a result, drug interactions may occur. Despite being legalized by the Thai Traditional Medical Council, the use of kratom as alternative medicine should be monitored by healthcare professionals. Anesthesia personnel should be especially cautious with patients who have a history of kratom use as ones who have used other addictive drugs before, during, or after surgery.